The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s12026-015-8661-1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of EV71 immunogenicity and protection against lethal challenge in a mouse model

Abstract: Circulating enterovirus 71 (EV71)-associated hand, foot, and mouth disease (HFMD) is a major public health problem in the Asian-Pacific region. An EV71 vaccine for HFMD prevention is currently being developed. However, viral determinants that could influence the vaccine's efficacy have not been well characterized. In this study, we isolated and characterized several EV71 strains that are currently circulating in northern and southern China. We determined that VP1 variation is a major determinant of EV71 immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In theory, preventing viral entry by blocking the “canyon”-receptor interaction would constitute the best way to cure or, at the least, control enteroviral infection. Previous studies have confirmed the role of VP1 variation as a major factor affecting enteroviral immunogenicity [ 9 , 41 ]. In the case of EVD68, the anti-rhinovirus drug pleconaril has already been shown to interact with VP1 and suppress viral pathogenesis in HeLa cells [ 20 ].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In theory, preventing viral entry by blocking the “canyon”-receptor interaction would constitute the best way to cure or, at the least, control enteroviral infection. Previous studies have confirmed the role of VP1 variation as a major factor affecting enteroviral immunogenicity [ 9 , 41 ]. In the case of EVD68, the anti-rhinovirus drug pleconaril has already been shown to interact with VP1 and suppress viral pathogenesis in HeLa cells [ 20 ].…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, the identification of the Clade B subclade indicates that such changes can occur very easily, since the four protein variations occurred within just a few years. In addition, we have previously observed that a single amino acid variation in EVA71 VP1 leads to significant differences in the host immune response [ 9 ]. Such occurrences in EVD68 (and probably other enteroviruses as well) poses challenges in the development of antivirals and/or vaccines, the success of which may require the development of novel strategies, such as the design of antiviral drugs that suppress the function of viral protease 3C [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain tissue samples (n = 3) were collected 3 and 12 hr after injection from each experimental group. The isolated samples were disrupted and homogenized with the grinding method (Chang et al, 2015). Total tissue RNA was extracted using Trizol reagent (Invitrogen), and viral RNAs in the infected brain tissues were determined by qRT-PCR using EV-D68-specific RNA.…”
Section: Immunoblottingmentioning
confidence: 99%
“…In mainland China, Taiwan and Singapore, EV71 whole-virus vaccines have been produced by various manufacturers. Two available inactivated EV71 vaccines have been approved by the China Food and Drug Administration, one produced by Sinovac Biotech Ltd. and the other by the Chinese Academy of Medical Science (all Beijing, China) (8)(9)(10). Currently, no effective treatment is available to treat severe EV71 infections, aside from symptomatic therapies (11).…”
Section: Introductionmentioning
confidence: 99%